Informal Clinical Integration in Medicare Accountable Care Organizations and Mortality Following Coronary Artery Bypass Graft Surgery. Issue 3 (March 2019) - Kim, Dennie; Funk, Russell J.; Yan, Phyllis; Nallamothu, Brahmajee K.; Zaheer, Aks; Hollingsworth, John M.
Abstract : Background: Accountable care organizations' (ACOs') focus on formal clinical integration to improve outcomes overlooks actual patterns of provider interactions around shared patients. Objective: To determine whether such informal clinical integration relates to a health system's performance in an ACO. Research Design: We analyzed national Medicare data (2008–2014), identifying beneficiaries who underwent coronary artery bypass grafting (CABG). After determining which physicians delivered care to them, we aggregated across episodes to construct physician networks for each health system. We used network analysis to measure each system's level of informal clinical integration (defined by cross-specialty ties). We fit regression models to examine the association between a health system's CABG mortality rate and ACO participation, conditional on informal clinical integration. Subjects: Beneficiaries age 66 and older undergoing CABG. Measures: Ninety-day CABG mortality. Results: Over the study period, 3385 beneficiaries were treated in 161 ACO-participating health systems. The remaining 49, 854 were treated in 875 nonparticipating systems or one of the 161 ACO-participating systems before the ACO start date. ACO systems with higher levels of informal clinical integration had lower CABG mortality rates than nonparticipating ones (2.8% versus 5.5%; P <0.01); however, there was no difference based on ACO participation for health systems with lower to relatively moderate informal clinical integration. Regression results corroborate this finding (coefficient for interaction between ACO participation and informal clinical integration level is −0.25; P =0.01). Conclusions: Formal clinical integration through ACO participation may be insufficient to improve outcomes. Health systems with higher informal clinical integration may benefit more from ACO participation. Abstract : Supplemental Digital Content is available in the text.